Experimental Investigation of The Real Time of Cooling Comparable to Temperature of An Air - Conditioner - Igoma, Emughiphel Nelson, ABDURRAHMAN ALI DUZE (IRE, 2022)
The experimental investigation of the real time of cooling comparable to temperature of an air - conditioner (1.5HP) attached to an office of size 6.83mx0.248m has been studied. It was found from the experiment that it takes (12) minutes to cool the Office-Room with the corresponding Air Conditioner Unit Temperature of 160C and as the Temperature of the Air Conditioner increases, the time taken for cooling increases as well. Moreso, for every 10C rise in the Temperature of the Air Conditioning, there is a corresponding rise of 1.2% time taken for the cooling. Recommendation of cleaning the Air Conditioner Filter in every two (2) weeks was made.
Keywords: Air Conditioner; Temperature; Time; Cooling; Thermometer